2020
DOI: 10.7860/jcdr/2020/43540.14083
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Occurrence of Bilateral Hypodontia and Microdontia in a Nonsyndromic Paediatric Patient: A Case Report

Abstract: Hypodontia is a developmental dental anomaly defined as the absence of one or more primary or permanent teeth excluding third molars. It can be associated with syndrome or nonsyndromic condition accompanied with other developmental dental anomalies like microdontia. Bilateral occurrence of hypodontia alongside microdontia is a rare condition. This case report presents a rare occurrence of bilateral hypodontia and microdontia in a nonsyndromic patient. Owing to its nonsyndromic background, other parameters like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[ 11 ] Anjali et al reported a rare case of bilateral occurrence of hypodontia and microdontia in nonsyndromic pediatric patients. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Anjali et al reported a rare case of bilateral occurrence of hypodontia and microdontia in nonsyndromic pediatric patients. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%